Extreme modulation of liquid crystal viscoelasticity via altering the ester bond direction. Issue 31 (20th July 2021) - Tang, Wentao; Deng, Minghui; Kougo, Junichi; Ding, Li; Zhao, Xiuhu; Arakawa, Yuki; Komatsu, Kenta; Tsuji, Hideto; Aya, Satoshi
Abstract : Extreme modulation of macroscopic viscoelastic properties (up to about 1000 times) in asymmetric liquid crystal dimers was successfully realized by altering only the ester bond direction in molecular structure. Abstract : The understanding of correlations between molecular details and macroscopic material behavior is a fundamental question of molecular chemistry/physics and offers practical interest in materials design with fine-property-tunability. Herein, we demonstrate extreme modulation of liquid crystal (LC) viscoelasticity triggered by a reversion of the ester bond direction in two series of sulfur-containing cyanobiphenyl-based LC dimers. They possess two oppositely directed ester linkages ( i.e., COO or OCO), namely COO n and OCO n, respectively, and different carbon atom numbers of the short alkylene spacers ( n = 4 and 6). Unexpectedly, it has been proven that the COO n homologs exhibit extraordinarily enhanced viscoelastic properties in the fluidic nematic (N) phase (up to about 1000 times) compared with their OCO n counterparts. Besides, dielectric spectroscopy revealed that the degree of the collective orientational fluctuation is significantly affected by reversing the ester bond direction, suggesting the existence of heliconical clusters embedded in the N state. Finally, we have proposed a novel eco-driving LC memory device based on a pulse-electric-field driving method using COO4 with an extremely high rotational viscosity.